Síndrome de Burnout em enfermeiros que atuam na Estratégia de Saúde da Família - Barros, Eveline de Oliveira (2016)
Burnout Syndrome (BS) is defined as a type of extended response to chronic emotional, psychosocial and interpersonal stressful factors related to work, when the means of combat and prevention are inadequate. This dissertation is composed of two papers: the first, theoretical, is called “Burnout Syndrome in nurses: bibliometric study of dissertations and theses in the Brazilian context”. Objective: To characterize the scientific production about BS in nurses. Methodology: This is a bibliometric study, composed of dissertations and theses, published in Brazil, from 2003 to 2015, available in the Digital Library of Theses and Dissertations of USP, CAPES Portal, Center for Studies and Research in Nursing, and Health Virtual Library. Results: It has identified 39 publications, with 27 dissertations and 12 theses. The greatest amount of works was developed in the Ribeirão Preto Nursing School, which belongs to the University of São Paulo. There was a prevalence of works produced by researchers with academic training in Nursing. The studies focused on the organization of work as a triggering factor of BS, as well as the prevalence and the risk of illness for this syndrome, and the most surveyed professionals were those who deal with hospital care. Conclusion: The studied scientific production emphasizes the correlation between BS and working conditions. One can realize the interest of researchers about this theme, although it has been observed a little expressive number of studies in the surveyed period. Introduction: The second paper is an original research, which is called “Prevalence of Burnout Syndrome and sociodemographic factors in nurses who work in the Family Health Strategy (FHS)”, whose objectives were: to evaluate the prevalence of BS in nurses who work in FHS; to characterize the presence of BS, according to the dimensions of the syndrome; and to check the association with some sociodemographic factors and working conditions. Methodology: This is a study of exploratorydescriptive nature, with quantitative approach, performed with nurses working in the Family Health Units (FHU) of the city of João Pessoa-PB. Data collection took place through a structured questionnaire and a validated instrument to evaluate BS. Data were statistically coded and analyzed. Results: Of the 193 nurses who comprise the study sample, 183 took part in the survey, with a predominance of female professionals, with steady partners and children, with Graduate degree. The age ranged between 24 and 69 years. Most nursing professionals have an average level for the Burnout Syndrome. Nevertheless, it is worth highlighting the worrying levels for the development of the syndrome, which are signs of vulnerability. Among the factors associated with burnout, it was found that this problem is more frequent in nurses without marital partners, with excessive workload, exceeding the 40 hours a week, worked in FHS, as well as for those who work in schedules beyond the full-time period. Conclusion: The data found are worrying, taking into account the perception of the prevalence and vulnerability of the Burnout Syndrome among the professionals who made up the sample of this study.